2020
DOI: 10.1007/978-3-030-36408-3_183
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal and Use of Green Binder for Use in Carbon Anodes in the Aluminium Industry

Abstract: Carbon anodes for aluminium production are produced from calcined petroleum coke (CPC), recycled anode butts and coal tar pitch (CTP). The CO 2 produced during anode consumption contributes to a substantial amount of the CO 2 footprint of this industrial process. Charcoal from wood has been suggested to partly replace coke in anodes but high porosity, low electrical resistivity and high ash content contributes negatively to final anode properties.In this work, charcoal from Siberian larch and spruce was produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…While a small percentage of biocoke blending can significantly improve sustainability metrics, doing so will help to evaluate the optimal blending ratio(s) for physical property improvements. Although some studies blended biocoke into pilot anodes at 5−10 wt %, 17 we used 10 and 27 wt % blend ratios in order to account for extra volatile losses. We used the particle size distributions mentioned in order to flow coke properly with the smaller-scale equipment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a small percentage of biocoke blending can significantly improve sustainability metrics, doing so will help to evaluate the optimal blending ratio(s) for physical property improvements. Although some studies blended biocoke into pilot anodes at 5−10 wt %, 17 we used 10 and 27 wt % blend ratios in order to account for extra volatile losses. We used the particle size distributions mentioned in order to flow coke properly with the smaller-scale equipment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18 CO 2 reactivity, real density, and electrical resistivity also relate directly to the crystalline texture. The excessive porosity of most biochars also interferes significantly with the density and CO 2reactivity 17 requirements.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They astutely noted that the high porosity of biocokes results in low densities, as well as a requirement for higher tar pitch percentages. Similarly to Monsen et al, Huang and co-workers , concluded that a 3 wt % blend of the biocoke fraction using fines could maintain acceptable anode properties, but blending 5 wt % of coke with biocoke significantly deviated from acceptable anode properties, including an increase of CO 2 reactivity beyond 25 mg/cm 2 h. Sommerseth et al went beyond mere testing of charcoal blends by increasing calcining temperatures to 1400 °C. This is beyond typical calciner temperatures, since it causes sulfur to escape quickly and thereby decreases density.…”
Section: Biobased Industrial Carbonsmentioning
confidence: 98%
“…Similar to the previous studies incorporating biocoke, they used a higher percentage of pitch (here, biopitch) for biocokebased anodes. Sommerseth's biocoke anode study 77 utilized a green binder, although no details about the green binder are given; it was found that green binders were detrimental to the anode performance. In Hussein et al's biopitch synthesis, 89 differences in properties were attained when varying the heat treatment rates of the starting fast pyrolysis bio-oil.…”
Section: ■ Biobased Industrial Carbonsmentioning
confidence: 99%